Economic recovery and inflation - Marek Dabrowski (Center for Social and Economic Research (CASE), 2018)
In the last decade, advanced economies, including the euro area, experienced deflationary pressures caused by the global financial crisis of 2007-2009 and the anti-crisis policies that followed - in particular, the new financial regulations (which led to a deep decline in the money multiplier). However, there are numerous signs in both the real and financial spheres that these pressures are disappearing. The largest advanced economies are growing up to their potential, unemployment is systematically decreasing, the financial sector is more eager to lend, and its clients - to borrow. Rapidly growing asset prices signal the possibility of similar developments in other segments of the economy. In this new macroeconomic environment, central banks should cease unconventional monetary policies and prepare themselves to head off potential inflationary pressures.
Keywords: E24; E31; E41; E51; E52; 330; monetary policy; inflation; economic growth; unemployment; money multiplier; money velocity